AUDIT LINGKUNGAN, PERLUKAH - Dul Muid (Universitas Islam Nahdlatul Ulama Jepara, 2004)
Environmental audit is one new type of audit in auditing. The existence of this type is now growing up in the business world because of the wider implementation of EMAS and ISO 14001 that has included c